The Arabidopsis ATP-BINDING CASSETTE Transporter ABCB21 Regulates Auxin Levels in Cotyledons, the Root Pericycle, and Leaves - Jenness, Mark K.; Carraro, Nicola; Pritchard, Candace A.; Murphy, Angus S. (Frontiers in Plant Science, 2019)
The phytohormone auxin plays significant roles in regulating plant growth and development. In Arabidopsis, a subset of ATP-BINDING CASSETTE subfamily B (ABCB) transporters participate in polar movement of auxin by exclusion from and prevention of reuptake at the plasma membrane. A previous analysis identified ABCB21 as a conditional auxin uptake/efflux transporter that regulates cellular auxin levels but clear physiological roles for ABCB21 in planta remain unknown. Here we show that ABCB21 maintains the acropetal auxin transport stream by regulating auxin levels in the pericycle. Loss of ABCB21 reduces rootward auxin transport and delays lateral root emergence. In seedling shoots, ABCB21 regulates mobilization of auxin from the photosynthetic cotyledons that is important for phototropic bending. In rosette leaves ABCB21 contributes to lateral auxin distribution. These results support a primary role for ABCB21 in regulating auxin distribution supplementary to the primary ABCB auxin transporters ABCB1 and 19.